A combined rotational mold for manufacturing a functional liver system. (July 2015) - Wang, Xiaohong; Huang, Yuanwen; Liu, Chang
A combined rotational mold system for liver manufacturing was prepared. The combined rotational mold system was composed of a branched internal mold, a basement mold, and a series of external molds with increasing diameters. Semi-spindle constructs, consisting of multiple cell types, such as adipose-derived stem cells and hepatocytes encapsulated in a fibrin hydrogel, were created by sequentially sandwiching cell-laden fibrin hydrogels between the combined rotational mold system based on the Weissenberg effect of non-Newtonian fluid. A spindle liver lobe precursor was constructed, with a multi-scale vascular network including arteries, veins, and capillaries, by integrating the two semi-spindle constructs together and coating the spindle construct with a layer of poly(DL-lactide-co-glycolide acid) solution. The spindle liver lobe precursor was characterized by a series of in vivo experiments. This first report is the preparation of a functioning complex organ, such as the liver, that was produced using an inexpensive, simple, and effective method.